Serotonin receptors - from molecular biology to clinical applications - Pytliak, M; Vargová, V; Mechírová, V; Felšöci, M (Physiological research, 2011)
Serotonin (5-hydroxytryptamine) is an ubiquitary monoamine acting as one of the neurotransmitters at synapses of nerve cells. Serotonin acts through several receptor types and subtypes. The profusion of 5-HT receptors should eventually allow a better understanding of the different and complex processes in which serotonin is involved. Its role is expected in the etiology of several diseases, including depression, schizophrenia, anxiety and panic disorders, migraine, hypertension, pulmonary hypertension, eating disorders, vomiting and irritable bowel syndromes. In the past 20 years, seven distinct families of 5-HT receptors have been identified and various subpopulations have been described for several of them. Increasing number of 5-HT receptors has made it difficult to unravel the role of 5-HT receptor subpopulations due to the lack of suitable selective agents. The present review describes the different populations and nomenclature of recently discovered 5-HT receptors and their pharmacological relevance.
Keywords: Humans; Serotonin; serotonin; Irritable Bowel Syndrome; Hypertension; schizofrenie; lidé; Receptors, Serotonin; Schizophrenia; migréna; zvířata; Vomiting; duševní poruchy; Synaptic Transmission; Migraine Disorders; nervový přenos; hypertenze; zvracení; Mental Disorders; syndrom dráždivého tračníku; receptory serotoninové; Animals